Meaning and Use of Haiku in the Game “Bungou to Alchemist” - Fairuz, Fairuz; Mutiara, Indah; Fadhilah, Fadhilah (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Haiku is a Japanese poem that is unique and uses a minimum of words, but it is still beautiful and has deep meaning. In this modern era, there are educational games that use haiku. One of them is the Japanese literary-themed game 'Bungou to Alchemist'. This game is about poets who are brought to life by alchemists to protect endangered Japanese literary works and eradicate the enemy, namely shinshokusha. Alchemist plays the role of librarian (shisho), who directs the bungou (poet) to eradicate the shinshokusha. One of them is Kawahigashi Hekigotou, a famous Japanese haiku poet. The aim of this study is to find the meaning contained in Hekigotou's four haiku that appear in the game and to identify the cause of the four haiku being used, using Roland Barthes' semiotic theory. This study used qualitative research methods. The result of the analysis is to show that Hekigotou's haiku used in this game has meaning related to life and is used to strengthen the conveying of Bungou to Alchemist ideas contained in the haiku in the form of a representation of Kawahigashi Hekigotou's feelings. At the same time, this game is a place for young people to get to know and learn literature, especially haiku.